Barriers and facilitators of access to sexual and reproductive health services among migrant, internally displaced, asylum seeking and refugee women: A scoping review. - Pengdewendé Maurice Sawadogo; Drissa Sia; Yentéma Onadja; Idrissa Beogo; Gabriel Sangli; Nathalie Sawadogo; Assé Gnambani; Gaëtan Bassinga; Stephanie Robins; Eric Tchouaket Nguemeleu (PLoS ONE)
Introduction Migrant, internally displaced, asylum seeking and refugee women experience ongoing risks of having their reproductive healthcare rights violated. This ever-increasing population also has limited access to sexual and reproductive health services. We conducted a scoping review to identify the barriers and facilitating factors when accessing sexual and reproductive health services for this specific population. Methods We searched the grey literature and queried eight bibliographic databases (Embase, Medline, Cinahl, Scopus, Science Direct, Web of Science, Hinari, and Cochrane Library) to extract articles published between January, 2000, and October, 2021. The extracted data were organized in a framework adapted from Peters et al. and then categorized as facilitators or barriers. We followed the Arksey and O'Malley framework and wrote the report according to the PRISMA-Scr recommendations. Results The search identified 4,722 records of which forty-two (42) met eligibility criteria and were retained for analysis. Ten (10) groups of factors facilitating and/or limiting access to sexual and reproductive health care emerged from the synthesis of the retained articles. The main barriers were lack of knowledge about services, cultural unacceptability of services, financial inaccessibility, and language barriers between patients and healthcare providers. Facilitators included mobile applications for translation and telehealth consultations, patients having a wide availability of information sources, the availability health promotion representatives, and healthcare providers being trained in cultural sensitivity, communication and person-centered care. Conclusion Ensuring the sexual and reproductive rights of migrant, internally displaced, asylum-seeking and refugee women requires that policymakers and health authorities develop intervention strategies based on barriers and facilitators identified in this scoping review. Therefore, considering their mental health in future studies would enable a better understanding of the barriers and facilitators of access to sexual and reproductive health services.